Keteladanan Dosen Fakultas Ekonomi UNP Dalam Meningkatkan Mutu Kegiatan Belajar Mahasiswa - Dessi Susanti; Armiati Armiati; Rose Rahmidani (Universitas Negeri Padang, 2018)
The purpose of this study was to: 1) identify exemplary lecturer Faculty of Economics, Universitas Negeri Padang as educators in improving the quality of student learning activities, 2) Analyze the contribution of exemplary lecturer at the Faculty of Economics Universitas Negeri Padang on the quality of student learning activities. This study uses a correlational approach, method of data collection that proportional sampling method, determination of the size of the sample using the formula slovin. Samples of 100 students from Faculty of Economics, Universitas Negeri Padang. The results of this study are 1) exemplary lecturer at the Faculty of Economics Universitas Negeri Padang as educators in improving the quality of student learning activities are currently on the criteria very well with the average indicators 4.2 and TCR 84; 2) exemplary lecturer at the Faculty of Economics Universitas Negeri Padang contributing to / effect on the quality of student learning activities with sig 0.001.